Desenvolvimento de oficina temática para o ensino de química utilizando fibra da casca do coco como tema gerador - Barcellos, Cátia Pereira (2019)
The reflections created in The reflections created in the educational field today bring us the perspective of how it occurs to the consolidation of the student's knowledge. If we can really use any technique or set of orchestrated actions that facilitates this learning, and that results in a knowledge that makes sense for that student. Based on this positive view, this paper aims to raise questions about the teaching of chemistry associated with the theme of coconut shell fiber reuse, using as methodology the development of thematic workshops. In order to apply this method, we sought as theoretical foundation the perspectives proposed by Marcondes, which brings in his works the characteristics necessary for the production of the workshops. Among these characteristics, there are the assumptions mentioned by Delizoicov, through the three pedagogical moments (3MP) that identifies as primordial elements for the construction of this methodology following the following steps: initial problematization, knowledge organization and the application of knowledge. Thus, we sought to bring these elements during the development of the workshop to compose the methodological path of the present research. The workplace selected for the workshops was the State School of Elementary and High School, located in the city of São Mateus, more specifically in the northern region of the state of Espírito Santo. In which, the author has been a teacher for approximately two years. The research was developed with students of the 1st grade of high school, because the theoretical concepts addressed in the workshop refer to this grade. As coconut fiber presents itself as a great filtering component, one possibility to exploit this feature is filter production. Therefore, the workshop developed was the construction of the filter using alternative materials, which allowed the retaking of chemical concepts such as substances, mixtures and the processes of separation of mixtures. The resources used for data collection were the application of questionnaires, textual production and the author's observation. Data processing follows the precepts developed by Bardin. The interventions carried out in the course of this research aim to contribute to the development of a dynamic class with the production of scientific knowledge, based on a regional theme and raise questions and discussions that contribute to the formation of citizens aware of their social role